A qualitative inquiry in understanding trusted media sources to reduce vaccine hesitancy among Kenyans - Fesshaye, Berhaun; Lee, Clarice; Paul, Alicia M.; Zavala, Eleonor; Singh, Prachi; Karron, Ruth A.; Limaye, Rupali J. (Frontiers in Communication, 2023)
COVID-19 vaccine rollout in Kenya has been challenged by both the supply of and demand for vaccines. With a third of the adult population classifying as vaccine hesitant, reaching vaccination targets requires an understanding of how people make decisions regarding vaccines. Globally, pregnant and lactating women have especially low uptake rates, which could be attributed to the “infodemic,” the constant rush of new information, as this group is vulnerable to misinformation and uncertainty. While presentation of COVID-19 vaccines in the media allows for easy access, these sources are also susceptible to misinformation. Negative and unfounded claims surrounding SARS-CoV-2 infection and COVID-19 vaccines contribute to vaccine hesitancy. Given the influence that the media may have on people’s attitudes towards vaccines, this study examines the relationship between the media and the vaccine decision-making process among pregnant and lactating women, healthcare workers, community members (male relatives, male neighbors, and gatekeepers), and policymakers in Kenya. Data were collected through in-depth interviews in urban and rural counties in Kenya to understand how media information was utilized and consumed. While healthcare workers were the most frequently cited information source for pregnant and lactating women, other healthcare workers, and community members, findings also show that the media (traditional, social, and Internet) is an important source for obtaining COVID-19 information for these groups. Policymakers obtained their information most frequently from traditional media. Ensuring that information circulating throughout these media channels is accurate and accessible is vital to reduce vaccine hesitancy and ultimately, meet COVID-19 vaccination goals in Kenya.